Examining the effectiveness of naloxone on opioid overdose: A structured review - Lee, Rachel; Ripley, Nicole (Université d'Ottawa | University of Ottawa, 2017)
Opioids are a psychoactive group of drugs that are used by approximately 35 million people worldwide, and account for majority of the 190 900 drug related deaths that occur annually.  Globally, there has been an increase in the usage of both synthetic and natural opioids, resulting in a higher number of deaths due to opioid overdose.  Naloxone, however, is an opioid antagonist that can be used to stop or reverse the effects of these potentially fatal drugs by increasing respiration, thus aiding in the avoidance of death.  This review, therefore, aims to assess the relationship between the usage of Naloxone and mortality rates due to opioid overdose among opioid users.  PubMed and Scopus databases were used to gather literature using the following key words: (“Naloxone” AND “overdose” AND “mortality rate”).  Articles were then included if they met the following criteria: written in English, published within the past 15 years, including humans only, and clinical trials, cohort studies, case-controls or systematic reviews. The reference lists were also reviewed, and taken into consideration for the selection process. Titles and abstracts of articles that met the inclusion criteria were then examined to determine relevance with regards to the scientific question. Finally, each article was read in full to obtain the total number of articles to be included in the structured review.  A total of 7 articles met the criteria and were used in the final structured review.  These studies indicate a positive association between the usage of Naloxone and decreased mortality rates due to opioid overdose, demonstrating that Naloxone is effective in reversing the effects of opioid overdose. Future research should compare mortality rates before and after the greater implementation of Naloxone treatments to determine if there has been a significant decrease in the number of deaths.